Ta‘rifāt Jāwī oleh Tuan Guru Haji Ibrahim Haji Jusoh (m. 1980): Satu Kajian Perkamusan Istilah Saintifik di Alam Melayu: Ta‘rifāt Jāwī by Tuan Guru Haji Ibrahim Haji Jusoh (d. 1980): An Analysis on the Lexicon of Scientific Terms in the Malay World - Ramli, Mohd Hilmi; Rosli, Muhammad Syukri (Afkar: Jurnal Akidah dan Pemikiran Islam, 2022)
The intellectual tradition in the Malay world is not isolated from the overall intellectual development in other parts of the Muslim world. The rapid and intense development of the intellectual development in this region especially during the 16th and 17th centuries contributed to the creation of specific and technical definitions in various sciences because scholars and thinkers require those specific and technical definitions in their teaching and articulation of ideas. The discovery of the manuscript Ta‘rifāt Jāwī written by Tuan Guru Haji Ibrahim Haji Jusoh (d. 1980), consisting of various technical terms in many sciences, which is similar to the popular work of Ta‘rifāt by al-Jurjānī (d. 1413), is a momentous finding in understanding the development of the creation of scientific dictionaries in the Malay world. This study intends to make a survey on the concept and history of dictionary-making with a reference to Ta‘rifāt Jāwī and to understand its contribution to the development and establishment of the intellectual tradition in this region particularly and the Muslim world in general. The technical terms will be selected and discussed their meanings. This study highlights a new intellectual and scientific horizon in dictionary-making and the development of the field of knowledge in the Malay world.